The Effectiveness of SPADA UNTIRTA in Promoting Self-Regulated Learning Outcome of the Economic Department Students at Sultan Ageng Tirtayasa University - Welliam Hamer; Dwi Rukmini; Mursid Saleh; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
This article aims at sharing to the readers on how SPADA UNTIRTA utilized in Sultan Ageng Tirtayasa University may enhance students' capacity for independent learning. Technology has advanced in recent years with its extensive usage in the global economy, tourism, and even education. To keep up with the increasingly technologically advanced age of globalization, technology-based media must be present in teaching-learning activities. E-learning media is one of the technology-based educational tools. Using internet or other computer network medium, e-learning enables the transmission of educational resources to students (Hartley, 2001). Teaching-learning activities previously restricted to campuses or schools are now possible anytime, anywhere with the aid of these technology-based media. One of the campus's electronic educational resources is SPADA. The goal of this strategy was to address some problems with higher education while allowing for seamless learning. The methods in which SPADA UNTIRTA can assist students in improving their ability to manage their own learning are referred to as ways in which SPADA UNTIRTA can be used as a tool for student self-integration. This implies that with SPADA UNTIRTA, students should be able to increase their level of independence in their learning activities. As a result, lecturers will only need to teach the material; additional learning tasks may be fully up to the students, providing them the opportunity to learn at their own speed. In this instance, SPADA UNTIRTA, a technology-based learning tool, is successful in promoting the students' independent study, especially in teaching and learning English for Specific Purposes.